AUTONOMÍA Y RESPONSABILIDAD EN EL APRENDIZAJE DE UNA LENGUA EXTRANJERA EN CONTEXTOS FORMALES. UNA EXPERIENCIA EN EL AULA - Rodríguez Parente, José Manuel (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
It is widely accepted that the existence of compulsory general education until the age of 16 -in practice up to 18- is a valuable achievement of our society. Students are offered the opportunity to complete their secondary education reasonably well prepared. Nevertheless, good intentions cannot always be realized due to a variety of circumstances: high student numbers, an overcrowded curriculum, and too few teacher-student contact hours per week are among the more serious obstacles. However, in this paper we will try to prove that in spite this unfavourable scenario a degree of learner autonomy is possible, and even necessary, in formal contexts of education, since we defend that “knowing” is good but “learning to find out” is even better.